2015
DOI: 10.1038/ncomms7396
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing and inhibiting stimulated Brillouin scattering in photonic integrated circuits

Abstract: On-chip nonlinear optics is a thriving research field, which creates transformative opportunities for manipulating classical or quantum signals in small-footprint integrated devices. Since the length scales are short, nonlinear interactions need to be enhanced by exploiting materials with large nonlinearity in combination with high-Q resonators or slowlight structures. This, however, often results in simultaneous enhancement of competing nonlinear processes, which limit the efficiency and can cause signal dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 64 publications
2
47
0
Order By: Relevance
“…In addition, has been suggested of using intense acoustic waves for the control of weak optical fields, for example, for frequency conversion [5,6], on-chip phase modulation [7], or nonreciprocal scattering of optical beams [8,9]. In particular, in nanophotonic structures, where photons and phonons are both strongly confined [10][11][12][13][14], such techniques represent a promising alternative to Kerr-or electro-optical modulation techniques for manipulating light [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, has been suggested of using intense acoustic waves for the control of weak optical fields, for example, for frequency conversion [5,6], on-chip phase modulation [7], or nonreciprocal scattering of optical beams [8,9]. In particular, in nanophotonic structures, where photons and phonons are both strongly confined [10][11][12][13][14], such techniques represent a promising alternative to Kerr-or electro-optical modulation techniques for manipulating light [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, we can certainly envisage mixed systems in which a classical coherent state phonon field interacts with non-classical photon states in order to transfer quantum information between different channels, and our treatment is ideal for studies at this quantum-classical boundary. As mentioned earlier, another avenue is the description of enhancement and inhibition of SBS through density of states engineering [52].…”
Section: Discussionmentioning
confidence: 99%
“…This infinite structure form is a good starting point for investigating the enhancement and suppression of Brillouin scattering by adjusting the matrix elements or the density of states of optical or acoustic modes. This is a technique that has recently begun to be explored in [52].…”
Section: Fermiʼs Golden Rulementioning
confidence: 99%
“…This, however, often results in simultaneous enhancement of competing nonlinear processes, which limit the efficiency and can cause signal distortion. Recently, we showed that the frequency dependence of the optical density of states near the edge of a photonic bandgap can be exploited to selectively enhance or inhibit nonlinear interactions on a chip [13]. We demonstrated this concept for SBS using a narrow band one dimensional photonic bandgap structure: a Bragg grating.…”
mentioning
confidence: 96%